Parenting programs for underserved populations: Issues of scientific integrity and social justice - Baumann, A; Mejia, A; Lachman, J; Parra-Cardona, R; Lopez-Zeron, G; Amador Buenabad, N; Vargas, E; Rodrigeuz, D (Springer Verlag, 2018)
Research suggests that parenting programs are effective for preventing behavioral and emotional difficulties in children, but a lot more attention needs to be paid to issues of context and culture during the development, testing and implementation of these interventions. The views and needs of underserved and disenfranchised communities in the US and the Global South are often not taken into account for the development and testing of interventions. The successful implementation of evidence-based interventions for vulnerable children and families in underserved and marginalized communities requires careful consideration of how existing paradigms of prevention, evaluation, and implementation science impact issues of social justice and equity. This paper will describe how a team of parenting program researchers has been collaborating with their partners globally in generating local knowledge by balancing the need for rigorous scientific methods with issues of power. Authors from the U.S., Latin America, Africa and Southeast Asia draw on their experiences regarding challenges and successes with issues regarding study design and measurement, the transferability and adaptation of interventions, and the dissemination and implementation of different parenting interventions while placing communities at the center of their efforts through participatory methods. We describe innovative approaches that span the continuum of intervention development, adaptation, optimization, evaluation, implementation, and scale up of different parenting programs for vulnerable children and families across the world. We conclude by offering specific and pragmatic recommendations to increase access of culturally relevant and effective parenting programs in these communities.